Overexpression of MYB transcription factor LrAN2 from Lycium ruthenicum activated the anthocyanin biosynthesis in the leaf and fruit of Lycium barbarum - Liang, Yunlong; Ma, Wenyan; Hu, Jinglei; Jiang, Yanyan; Li, Shiming; Li, Yun; Bao, Xuemei; Cao, Dong; Liu, Baolong (Biotechnology, biotechnological equipment, 2024)
AN2 was thought to be the key gene inducing the fruit color differentiation of Lycium barbarum and Lycium ruthenicum, but there was no direct evidence. In this study, AN2 from L. ruhtenicum was overexpressed in L. barbarum to conform its function in regulating anthocyanin biosynthesis. The results showed that the stems, leaves, and fruits of transgenic plants were purple and contained significantly higher anthocyanin levels compared to the wild-type plants. Transcriptome analysis of leaf and fruit identified 5,832 differentially expressed genes (DEGs) in leaves and 2,029 DEGs in fruits, with 910 genes common to both tissues. GO and KEGG pathway enrichment analyses indicated a significant impact of LrAN2 on flavonoid biosynthesis and anthocyanin biosynthesis. The structural genes involved in the anthocyanin pathway, such as 4CL, CHS, F3H, F3'5'H, DFR, ANS, and UFGT, were up-regulated in transgenic lines, while the expression of transcription factors bHLH and WD40 were remained unchanged. These findings confirm the role of LrAN2 in the color differentiation of L. barbarum and L. ruthenicum and highlight its potential for the genetic enhancement of anthocyanin content in L. barbarum and other Solanaceae species.